2008
DOI: 10.1002/tox.20388
|View full text |Cite
|
Sign up to set email alerts
|

Bioconcentrations of metals (Fe, Cu, Zn, Pb) in earthworms (Eisenia fetida), inoculated in municipal sewage sludge: Do earthworms pose a possible risk of terrestrial food chain contamination?

Abstract: Efforts have been made to evaluate the possible risks of metal bioaccumulation in composting earthworms during vermicomposting of hazardous wastes, e.g., sewage sludge. The sewage sludge was diluted by mixing cow dung in different proportions, and vermicomposted sludge as well as inoculated earthworms were analyzed for metal (Fe, Cu, Zn, Pb) contents. The sludge processed by worms showed a significant reduction in concentration of metals, Cu (29.4-51.6%), Fe (13.1-19.9%), Zn (15.2-25.8%), and Pb (4.6-46.9%), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 21 publications
2
24
3
1
Order By: Relevance
“…Past studies have found insects to uptake bulk metals from soil [42][43][44]. In the present study, an uptake of silver from Ag NPs as a function of concentration of Ag NPs in soil was observed.…”
Section: Uptake Of Silver From Ag Nps In Soil By Insectssupporting
confidence: 59%
“…Past studies have found insects to uptake bulk metals from soil [42][43][44]. In the present study, an uptake of silver from Ag NPs as a function of concentration of Ag NPs in soil was observed.…”
Section: Uptake Of Silver From Ag Nps In Soil By Insectssupporting
confidence: 59%
“…Many studies have reported that concentrations of metals (such as Cd, Cu, Fe, Pb, and Zn) in whole worms are directly related to availability of metals in soil (Morgan and Morgan, 1998;Suthar and Singh, 2009;Nannoni et al, 2014). The uptake of Cd and Pb in earthworms was even sometimes characterized by linear pattern, due to their commonly very slow or non-existent elimination (Giska et al, 2014).…”
Section: Patterns Of Variability Of Metal/metalloid Concentrations Inmentioning
confidence: 99%
“…The specific aims of the study were: (1) to define the level of metal/metalloid contamination of depot sludge; (2) to establish a baseline for metal/metalloid elements in whole earthworm tissues, as well as for the first time in the soluble tissue fraction, based on the measured concentrations in non-exposed organisms; and (3) to study the patterns of metal/metalloid variability in earthworms after exposure to depot sludge. Commonly, only few selected elements are monitored in the earthworms, such as Cd, Cu, Fe, Pb, and Zn (Carpené et al, 2006;Kamitani and Kaneko, 2007;Suthar and Singh, 2009;Li et al, 2010;Giska et al, 2014). Only seldom studies extend on larger number of elements (Nahmani et al, 2007b;Nahmani et al, 2009;Nannoni et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Earthworms are of major importance in soil processes (Carnovale et al 2015). They perform essential role for soil health, microbial structure, nutrients and carbon cycling (Toyota and Kimura 2000;Fahey et al 2013), indicating active role in agricultural restoration, environmental indicators and bioconcentration and bioavailability for contamination (Pass et al 2015;Suthar and Singh 2009). However, exotic earthworm invasion resulted in significant negative impact on soil profiles, understory plants, fungus and nutrient cycling in non-native earthworm area (Holdsworth et al 2007;Suarez et al 2004;Belote and Jones 2009).…”
Section: Introductionmentioning
confidence: 99%